Adsorption of Different Ionic Types of Polyacrylamide on Montmorillonite Surface: Insight from QCM-D and Molecular Dynamic Simulation - Xiaomin Ma; Xiaosong Sun; Ming Chang; Qingxia Liu; Xianshu Dong; Yuping Fan; Ruxia Chen (Molecules, 2023)
This study investigates the interaction between montmorillonite and polyacrylamide (PAM) with different ionic types using quartz crystal microbalance with dissipation monitoring (QCM-D) and molecular dynamics (MD) simulations. The goal was to understand the effect of ionicity and ionic type on polymer deposition on montmorillonite surfaces. The results of the QCM-D analysis showed that a decrease in pH led to an increase in the adsorption of montmorillonite on the alumina surface. The ranking of adsorption mass on alumina and pre-adsorbed montmorillonite alumina surfaces was found to be cationic polyacrylamide (CPAM) > polyacrylamide (NPAM) > anionic polyacrylamide (APAM). The study also found that CPAM had the strongest bridging effect on montmorillonite nanoparticles, followed by NPAM, while APAM had a negligible bridging effect. The MD simulations showed that ionicity had a significant influence on the adsorption of polyacrylamides. The cationic functional group N(CH3)3+ had the strongest attraction interaction with the montmorillonite surface, followed by the hydrogen bonding interaction of the amide functional group CONH2, and the anionic functional group COO- had a repulsive interaction. The results suggest that at high ionicity levels, CPAM can be adsorbed on the montmorillonite surface, while at low ionicity levels, APAM may still be adsorbed with a strong coordination trend.